Population genomic analysis provides evidence of the past success and future potential of South China tiger captive conservation - Chen Wang; Dong Dong Wu; Yao Hua Yuan; Meng Cheng Yao; Han Jianlin; Ya Jiang Wu; Fen Shan; Wan Ping Li; Jun Qiong Zhai; Mian Huang; Shi Ming Peng; Qin Hui Cai; et al. (Springer, 2023)
Background Among six extant tiger subspecies, the South China tiger (Panthera tigris amoyensis) once was widely distributed but is now the rarest one and extinct in the wild. All living South China tigers are descendants of only two male and four female wild-caught tigers and they survive solely in zoos after 60 years of effective conservation efforts. Inbreeding depression and hybridization with other tiger subspecies were believed to have occurred within the small, captive South China tiger population. It is therefore urgently needed to examine the genomic landscape of existing genetic variation among the South China tigers.